Residual effect of Citrus sinensis and Syzygium aromaticum essential oils in association with temephos on Aedes aegypti Linn. larvae (Diptera: Culicidae) in laboratory (Research, Society and Development, 2022)
The increase of Ae. aegypti resistance to conventional insecticides and growing public concern about the environmental impact has resulted in the development of alternatives to mosquito control. Thus, the use of essential oils (EOs) in combination with larvicides may be a strategy used to reduce the phenomenon of resistance. Controlling larvae with insecticides for a prolonged period is important for interrupting transmission of vector-borne viruses, as long lasting larvicidal formulations reduce health agents visits with a consequent reduction in the global cost for controlling mosquito spread. Previous studies have shown that synergistic interactions between temephos and EOs exhibited increased larvae lethality when compared to temephos alone. Therefore, the goal of this work was to evaluate the residual effects of associations between temephos and EOs of Citrus sinensis and Syzygium aromaticum homogenized in hydrogel and impregnated in ceramic supports on Ae. aegypti larvae. After application of the products in 1,000 mL beakers, 25 larvae were deposited in each beaker and every five days half of the beakers were emptied to 200 mL, the original volume was replaced and new batches of larvae were added. Mortality was observed after 48 h of larval exposure. There was equivalence in the residual effect of association temephos/EOs when compared with temephos alone.